Kebijakan Tata Kelola Limbah Rumah Tangga, dalam Rangka Pencegahan Pencemaran Lingkungan (Studi Kasus di Lingkungan Kelurahan Pedungan Kecamatan Denpasar Selatan Kota Denpasar) - Pande Nyoman Jaya Budiarta; . I Nyoman Putu Budiartha; I Nyoman Gede Sugiartha (Warmadewa Press, 2022)
The increase in the total population is in line with the increase in the total waste created. Garbage is the main problem observed through the development of the total population, so that policies are needed to overcome this, one of which is the policy of managing household waste. The purposes of this study are to reveal the policy of the Head of Pedungan Village in managing household waste in Pedungan Village and the application of Denpasar Mayor Regulation No. 11 of 2016 concerning procedures for processing and disposing of waste in Denpasar City, especially in Pedungan Village. The method in this research is empirical law which approaches facts, cases, as well as sociological, conceptual and statutory approaches. The technique of collecting legal materials is obtained directly through respondents through interviews. Sources of legal materials used are primary and secondary, then analyzed descriptively qualitatively. The findings indicate that in the Denpasar City area, especially in the Pedungan Village area, it has been implemented related to managing household waste that prevents environmental pollution through the issuance of policies related to the Decree of the Head of the Pedungan Village Number: 660/04/I/2019 concerning the Management Structure of the Asri Waste Bank in the Kelurahan. shelter. The implementation of this policy needs to be improved because public knowledge and awareness is still low on household waste management